Timing of The First Zygotic Cleavage Affects Post-Vitrification Viability of Murine Embryos Produced In Vivo - Wan-Hafizah Wan Jusof (International Journal of Fertility and Sterility, 2015)
Background Timing of the first zygotic cleavage is an accurate predictor of embryo quality. Embryos that cleaved early (EC) have been shown to exhibit higher develop- mental viability compared to those that cleaved at a later period (LC). However, the vi- ability of EC embryos in comparison to LC embryos after vitrification is unknown. The present study aims to investigate the post-vitrification developmental viability of murine EC versus LC embryos. Materials and Methods In this experimental study, female ICR mice (6-8 weeks old) were superovulated and cohabited with fertile males for 24 hours. Afterwards, their ovi- ducts were excised and embryos harvested. Embryos at the 2-cell stage were catego- rized as EC embryos, while zygotes with two pronuclei were categorized as LC embryos. Embryos were cultured in M16 medium supplemented with 3% bovine serum albumin (BSA) in a humidified 5% CO2atmosphere. Control embryos were cultured until the blastocyst stage without vitrification. Experimental embryos at the 2-cell stage were vitri- fied for one hour using 40% v/v ethylene glycol, 18% w/v Ficoll-70 and 0.5 M sucrose as the cryoprotectant. We recorded the numbers of surviving embryos from the control and experimental groups and their development until the blastocyst stage. Results were analyzed using the chi-square test. Results A significantly higher proportion of EC embryos (96.7%) from the control group developed to the blastocyst stage compared with LC embryos (57.5%, P < 0.0001). Similarly, in the experimental group, a significantly higher percentage of vitrified EC embryos (69.4%) reached the blastocyst stage compared to vitrified LC embryos (27.1%, P < 0.0001). Conclusion Vitrified EC embryos are more vitrification tolerant than LC embryos. Prese- lection of EC embryos may be used as a tool for selection of embryos that exhibit higher developmental competence after vitrification.